Waste-to-Energy (WTE) network synthesis for Municipal Solid Waste (MSW) - Ng, Wendy; Lam, H.; Varbanov, P.; Klemes, J. (Elsevier, 2014)
MSW has been identified as one of the alternative energy sources that can be used for electricity and/or power generation. This appears to be one enhanced channel to tackle MSW disposal problem. WTE concept is incorporated into the MSW management system in this work. The integrated system is modelled to study its practicability and significance. The proposed model is illustrated with a case study involving the supply network design and the utilisation of MSW from urban sources. The modelling steps involve the generation of a superstructure, mathematical model construction, optimisation and solution interpretation. The MSW availability and its utilisation are investigated through its supply network design. Optimal locations of processing hubs and facilities are determined. Following this, boundaries and sizes of the processing hubs are calculated. The benefits of WTE strategy from MSW is analysed and its energy generation potential is demonstrated. This WTE strategy acts as one potential MSW management scheme for all interested parties.